2007
DOI: 10.1007/s00113-007-1263-1
|View full text |Cite
|
Sign up to set email alerts
|

Verletzungen und Verletzungsrisiko beim Ski- und Snowboardsport

Abstract: There was no increase in injury risk at the pistes in recent years. The use of protectors has a positive effect and should be supported in the future too.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 0 publications
0
9
0
3
Order By: Relevance
“…Although the injury risk of less than 2 injuries per 1000 ski days [ 2 , 3 ] seems low, the total number of injuries per year remains high because of the huge population at risk. In recreational alpine skiing, severe injuries are often related to excessive speed [ 4 , 5 ]. Studies measuring speeds on ski slopes with a radar speed gun reported a mean skiing speed of 45–48 km/h (28–30 mph) depending on several factors [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the injury risk of less than 2 injuries per 1000 ski days [ 2 , 3 ] seems low, the total number of injuries per year remains high because of the huge population at risk. In recreational alpine skiing, severe injuries are often related to excessive speed [ 4 , 5 ]. Studies measuring speeds on ski slopes with a radar speed gun reported a mean skiing speed of 45–48 km/h (28–30 mph) depending on several factors [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, lower temperatures and bad weather conditions are associated with a higher injury risk on ski slopes. 3,31 Obtaining information about the weather and snow conditions prior to touring could therefore be a preventive measure. Inattentiveness was found to be another cause for injuries in this study.…”
Section: Discussionmentioning
confidence: 99%
“…sehr wenig Ermüdung an (p = 0,910). [22], dass die Verletzungswahrscheinlichkeit im Laufe einer Skiwoche in den ersten drei Tagen konstant ist und dann kontinuierlich absinkt. Daher scheint es präventiv sinnvoll, sich im Wintersporturlaub besonders an den ersten beiden Tagen schrittweise an die spezifischen Begebenheiten wie Höhenlage und Witterungsbedingungen sowie an die ungewohnte körperliche Betätigung beim Skifahren bzw.…”
Section: Ergebnisseunclassified